Assessing momentary user experience with conversational agents using an electroencephalography device - Brock, Laís Andressa (2020)
All User Experience aspects can play a part in eliciting feelings about a certain product. Momentary UX refers to any changes of feelings during the interaction at the moment it happens. To be able to evaluate Momentary UX, electrophysiological measures have been used. The aim of this study is to compare Momentary UX episodes while participants interacted with different conversational agents. Thirty-six participants of both genders were divided into three groups to perform the same tasks. First group was the control group using Google's search engine in oogle's Chrome browser; the second group used Google's Assistant using keyboard and the third used Google's Assistant using voice commands. An Emotiv Insight device and UX questionnaires were used to collect data. The results between groups from both the electroencephalogram and questionnaires were consistent and differences were discussed. There was difference in the user's Momentary UX regarding their excitement levels collected by the EEG when they were interacting with conversational agents by voice. The main contribution is using electroencephalography as a instrument to measure Momentary UX and inferring that the interaction using voice shows emotional particularities.